2017
DOI: 10.4012/dmj.2016-305
|View full text |Cite
|
Sign up to set email alerts
|

SEM evaluation of the precision of fit of CAD/CAM zirconia and metal-ceramic posterior crowns

Abstract: The purpose of this study is to evaluate the precision of fit of posterior crowns made from three commercial CAD/CAM zirconia ceramics and conventional metal-ceramic technique. The external and internal marginal fit of the crowns was evaluated using direct SEM-based measurements. The data were subjected to Kruskal-Wallis, multicomparison post hoc analysis and Wilcoxon rank sum tests (α=0.05). Significant differences were observed for the external (p<0.002) and the internal (p<0.0001) marginal evaluation among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 32 publications
0
23
0
4
Order By: Relevance
“…In this study, we measured the marginal gaps by optical microscope due to its non‐destructive nature, feasibility, and practicality. Some studies confirmed the similarity between direct external and internal viewing techniques in measuring marginal fit of zirconia crowns and indicated that using external viewing is adequate and accurate for measuring the marginal fit without needing to destroy the specimens . Comparing the marginal gap results from different studies is difficult because of the high variability in the methodologies, including using different fabrication systems, types of cements, and methods for assessing the fit …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we measured the marginal gaps by optical microscope due to its non‐destructive nature, feasibility, and practicality. Some studies confirmed the similarity between direct external and internal viewing techniques in measuring marginal fit of zirconia crowns and indicated that using external viewing is adequate and accurate for measuring the marginal fit without needing to destroy the specimens . Comparing the marginal gap results from different studies is difficult because of the high variability in the methodologies, including using different fabrication systems, types of cements, and methods for assessing the fit …”
Section: Discussionmentioning
confidence: 99%
“…Microleakage at marginal interfaces may cause restoration failure due to the dynamic passage of bacteria, oral fluids, molecules, and ions between the interface of the restoration and tooth, causing secondary caries and discoloration of margins as well as tooth hypersensitivity. [4][5][6][7][8][9][10][11][12] A recent systemic review reported that the estimated annual complication rate for single unit zirconia crowns was 0.09% for secondary caries and 0% for marginal staining. 13 No information was provided regarding the incidence of hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical marginal fit of the restorations was assessed by measuring the external and marginal vertical gap. The measures were the vertical distance between the crown margin and the prepared cavosurface angle following previous studies at six points for each abutment, making three marks at the buccal and at the lingual surface of the die, using a profile projector with a 4× magnification (Toupview V.x643.7.6701, Photonics Co., Ltd., Suzhou, China) [20]. A total of sixty measurements were recorded for the FDPs (Figure 2a,b).…”
Section: Methodsmentioning
confidence: 99%